1993
DOI: 10.1143/jjap.32.327
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Scale E-Beam Resist Development Simulation for Pattern Fluctuation Analysis

Abstract: To better understand nanometer scale pattern fluctuation in lithography, we present a new model for electron-beam exposed (poly)methyl-methacrylate resist development, which considers the molecular scale material structure. The polymer chains in the resist are represented as spheres with a radius proportional to the square root of the chain length. Monte Carlo electron scattering simulation in the resist gives the local absorbed energy, which in turn sets the local molecular weight distribution. The developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…Because of its importance in the last few years, several publications discuss the problem of roughness. [1][2][3][4][5][6][7][8][9] Surface roughness ͑SR͒ appears after the spin coating of the photoresist film, while line edge roughness ͑LER͒ appears after the development of the microstructure. However, the two phenomena are closely related.…”
Section: Framework For Sr and Ler Studiesmentioning
confidence: 99%
“…Because of its importance in the last few years, several publications discuss the problem of roughness. [1][2][3][4][5][6][7][8][9] Surface roughness ͑SR͒ appears after the spin coating of the photoresist film, while line edge roughness ͑LER͒ appears after the development of the microstructure. However, the two phenomena are closely related.…”
Section: Framework For Sr and Ler Studiesmentioning
confidence: 99%
“…The LER of nonchemically amplified resists has been studied with regard to molecular weight, polydispersity, and the structure of base polymers, 1,12 and by simulations of the development process. 13 Though the relationship between these factors and LER were demonstrated, the origin of LER has not yet been definitely clarified. It is thought that LER is generated through inhomogeneous dissolution behavior at the nanometer scale.…”
Section: Introductionmentioning
confidence: 99%
“…They are mainly evaluations of the linewidth fluctuation of resist patterns in connection with the resist molecular size and its molecular weight distribution [3,4]. Recently, we found that the linewidth fluctuation is caused by granular structures in the resist films [5].…”
Section: Introductionmentioning
confidence: 99%